2022
DOI: 10.1021/acsanm.1c03988
|View full text |Cite
|
Sign up to set email alerts
|

A Triple Bioinspired Surface Based on Perfluorodecyl Trimethoxysilane-Coated ZnO Nanosheets for Self-Driven Water Transport in a Flow Channel

Abstract: Water management is important for the bipolar plates of proton-exchange membrane fuel cells (PEMFCs), and active drainage is a desirable feature for the design of bipolar plate channels. Herein, inspired by natural micro-nanostructures, a triple bioinspired surface has been fabricated, which combines the advantages of both superhydrophobic and superhydrophilic surfaces. The superhydrophobic surface (FZnO@CA-GS) is prepared by PFTS (perfluorodecyl trimethoxysilance) coating on ZnO nanosheet-decorated arrays of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…50,68 Only the hydrophilic surface of the integument of the desert beetle constitutes the source of inspiration and a hydrophilic coating is applied within the channels of a conventional flow-field; the network of micro-sized grooves that transports the water from its integument to its mouth is not considered. 50,68 As a result, water removal from such bioimitating flow-fields still relies on pressure drop (gas transport) with questionable stability, reproducibility, and scalability, as, at larger scales, pressure drop within the flow-field significantly increases, thus enhancing parasitic energy losses. 31 In our work, a thin graphite plate with laser-engraved microchannel structure is engineered via a compact laser micromachining system and installed in a commercial flowfield (serpentine and parallel) and our best performing lunginspired flow-field (N = 4) based PEMFCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50,68 Only the hydrophilic surface of the integument of the desert beetle constitutes the source of inspiration and a hydrophilic coating is applied within the channels of a conventional flow-field; the network of micro-sized grooves that transports the water from its integument to its mouth is not considered. 50,68 As a result, water removal from such bioimitating flow-fields still relies on pressure drop (gas transport) with questionable stability, reproducibility, and scalability, as, at larger scales, pressure drop within the flow-field significantly increases, thus enhancing parasitic energy losses. 31 In our work, a thin graphite plate with laser-engraved microchannel structure is engineered via a compact laser micromachining system and installed in a commercial flowfield (serpentine and parallel) and our best performing lunginspired flow-field (N = 4) based PEMFCs.…”
Section: Discussionmentioning
confidence: 99%
“…This is demonstrated in recent reports mimicking the water drinking mechanism of certain desert beetles, which bears similarities to the one of lizards living in arid environments, to improve the water management within a PEMFC. 50,68 Only the hydrophilic surface of the integument of the desert beetle constitutes the source of inspiration and a hydrophilic coating is applied within the channels of a conventional flow-field; the network of micro-sized grooves that transports the water from its integument to its mouth is not considered. 50,68 As a result, water removal from such bio-imitating flow-fields still relies on pressure drop (gas transport) with questionable stability, reproducibility, and scalability, as, at larger scales, pressure drop within the flow-field significantly increases, thus enhancing parasitic energy losses.…”
Section: Discussionmentioning
confidence: 99%
“…The other way is to reduce the sweat residue on both the skin and the fabric, thereby reducing the amount of heat lost by evaporation. To reduce the sweat residue on the skin, materials with directional moisture transport properties (namely, fluid diodes) that combine hydrophilic and hydrophobic sections (Janus materials), as well as all-hydrophilic materials, have been proposed and implemented to transfer sweat from the skin side to the outer side of the fabric. These materials can provide a degree of dryness to the individual, but sweat is still present at the hydrophilic layer and evaporation of the residual sweat consumes body heat, which decreases the warming capability of the fabric. , Few studies have reported sweat residue reduction in both the skin and the fabric. Unlike a liquid diode with a hydrophilic layer, a new kind of liquid diode fabric made entirely of all-hydrophobic materials was previously reported by the authors .…”
Section: Introductionmentioning
confidence: 99%
“…[12] Therefore, modulation of surface wettability or directional transport of droplets can be achieved by controlling the interaction between the micro-nanosurface structure and droplets. For example, under external stimuli such as force, temperature, humidity, pH, light, electricity, and magnetism, the wettability [13] and adhesion [14] of the material surface change, which can achieve hydrophilic and hydrophobic conversion, [15] droplet/microfluidic transport, [16] and surface adhesion adjustment. [17] In addition to the wettability, the surface micro-nano array structure can also be converted into detectable electrical signals under external stimulation, which can decode the information carried by the feedback.…”
mentioning
confidence: 99%